The Effect of a Cheese Co-product in Nursery Pig Diets from Sows Fed with and Without Cheese Co-Product in Lactation - Grady A. Privett; Diego A. Lopez; Jason C. Woodworth; Katelyn N. Gaffield; Jordan T. Gebhardt; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 395 weanling pigs (DNA 241 × 600; initially 12.7 lb) were used to evaluate the effects of previous sow lactation feed treatment (control vs. cheese co-product) and nursery diets formulated with or without a cheese co-product on growth performance in a 35-d trial. Pigs were weaned at approximately 19 d from sows fed lactation diets either with or without 4% cheese co-product (Pro88, Keys Manufacturing, Paris, IL). Pigs were placed in pens (five pigs per pen) within sow treatment and were randomly assigned one of two dietary nursery treatments. There were 19 to 21 replications per treatment. Nursery treatments included either a control diet or the control diet with 4% added cheese co-product fed in phases 1 and 2, followed by a common diet fed to all pigs in phase 3. Dietary treatments were arranged in a 2 × 2 factorial with main effects of sow diet (with or without cheese co-product) and nursery diet (with or without cheese co-product). There were no sow-diet-by-nursery-diet interactions observed throughout the study. Offspring from sows fed cheese co-product were heavier (P < 0.001) at weaning than those not fed cheese co-product, and this weight advantage was maintained throughout the study. There was a tendency (P = 0.058) for fewer piglets fed the cheese co-product in the nursery to lose body weight from d 0 to 3 after weaning, regardless of the previous sow treatment. During the experimental period (d 0 to 21 post-weaning), pigs weaned from sows fed the cheese co-product tended to have improved (P = 0.079) F/G, leading to a tendency for improvement (P = 0.059) in overall F/G. There were no effects on ADG or ADFI. In addition, during the experimental period, feeding the cheese co-product in the nursery diet improved (P = 0.008) F/G compared to pigs fed the control diet, resulting in an improvement (P = 0.032) in overall F/G. There were no effects on ADG or ADFI. In conclusion, F/G tended to be improved in offspring weaned from sows fed the cheese co-product, and feeding it in phase 1 and 2 nursery diets improved F/G and tended to reduce the number of pigs that lost weight in the first three days after weaning.
Keywords: Cheese co-product; lactation; nursery pigs